Enterotoxins A and B produced by Staphylococcus aureus increase cell proliferation, invasion and cytarabine resistance in acute myeloid leukemia cell lines - Seyhan Turk; Hatice Yanpar; Ayriana Safari Baesmat; Secil Demirkol Canli; Olgu Erkin Cinar; Umit Yavuz Malkan; Can Turk; Ibrahim Celalettin Haznedaroglu; Gulberk Ucar (Heliyon, 2023)
As in the case of cancer, the risk of infection increases when the host's immune system is not working properly. It has been shown that toxins produced by the bacteria responsible for bacterial infections can alter the properties of cancer cells as well as their sensitivity to chemotherapy agents. Staphylococcus aureus (S. aureus) is one of the most prevalent pathogens in acute myeloid leukemia (AML) patients and it produces several virulence factors, including Staphylococcal enterotoxin A (SEA) and Staphylococcal enterotoxin B (SEB). Cytotoxicity, transwell migration, invasion assays, and various transcriptomic and gene set enrichment (GSE) analyses were used to determine how SEA and SEB alter cell proliferation, migration, invasion, and Cytarabine (Cyt) resistance in AML cell lines. The treatment of AML cell lines with SEA/SEB caused an increase in cell proliferation and Cyt resistance. Toxins enhanced the proclivity of cells to migrate and invade, with around 50% of cells in the presence of SEA and SEB. Transcriptomic and gene set enrichment analyses, and subsequent PCR validations showed dysregulation of immune related genes and genesets. Apparently, this allows AML cells to escape and survive the undesirable environment created by toxins, possibly via the ER stress signaling pathway. Therefore, SEA and SEB can significantly alter the characteristics of AML cancer cells and evaluation of alterations in responsible immune genes and pathways may be crucial for controlling the progression of cancer. In addition, our results suggest that there may be a strong interaction between the immune related pathways and the ER signaling pathway.